The Latin American Exile Experience from a Gender Perspective: A Psychodynamic Assessment - Freire, Marlinda (Refuge: Canada’s Journal on Refugees, 1995)
Organized violence against individuals leads to a breaking point in their lives. Among other traumas, it results from exposure to death fears, an inability to use culturally acquired coping and grief reactions, a loss of meaning (loss of individuality in the face of annihilation), numbed and constricted personalities, fixation on an unfinished past, and severed bonds with common heritage (Dasberg 1986).